Simulation of microwave's heating effect on coal seam permeability enhancement - Huang, J.; Xu, Guang; Chen, Y.; Chen, Z. (Elsevier, 2018)
© 2018 As hydraulic fracturing was forbidden in some countries due to possible negative environmental impacts and enhanced coalbed methane (ECBM) was restricted by in-situ conditions, microwave heating was proposed to enhance coalbed permeability. One of the mechanisms of improving coal permeability with microwave irradiation is that thermal expansion caused by microwave heating. To study the influence of microwave's heating effect of coal samples, the simulations were conducted using a coupled electromagnetic, thermal and mechanical model in this paper. The temperature, Von-Mises stress and strain distribution of coal sample are recorded every 10 s. The permeability distribution is also obtained based on the relationship between strain and permeability from articles. It was found that volume average temperature, stress, strain and permeability increase almost linearly with time. The average permeability increased from 1.65 × 10-16m2to 3.63 × 10-16m2under 2.45 GHz and 500 W microwave radiation after 300 s. The significant increase proved microwave to be effective in coal seam permeability enhancement.